A terahertz frequency band high dielectric, low loss composite material and preparation method thereof
By using multi-size, multi-component modified high-dielectric constant inorganic fillers and modified insulating materials in the terahertz frequency band, combined with melt blending and thermoforming technology, the problem of difficulty in achieving high dielectric constant and low loss in the prior art is solved, and efficient dielectric performance regulation is achieved to meet the needs of high-frequency communication devices.
Patent Information
- Application Number
- CN202411825891.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-12
AI Technical Summary
In the terahertz band, it is difficult for existing polymer composites to achieve high dielectric constant and low loss at the same time, and the prior art mainly focuses on the low-frequency microwave band when regulating dielectric performance, and the theory is unclear.
Multi-size and multi-component modified high-dielectric constant inorganic fillers, combined with smaller-sized modified insulating materials, the high-dielectric material particle spacing arrangement is achieved through melt blending and thermoforming technology, blocking electric field coupling, increasing dielectric constant and maintaining low losses.
It realizes excellent performance of high dielectric constant and low loss tangent in the terahertz band, meets the application needs of miniaturized and low loss high-frequency communication devices, improves the amplitude of the dielectric constant and reduces losses.
Smart Images

Figure CN119286139B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high dielectric composite materials, and in particular, relates to a terahertz frequency band high dielectric, low loss composite material and a preparation method thereof. Background Art
[0002] Polymer dielectric materials are widely used in the development and design of terahertz wave communication devices. The dielectric constant and loss tangent of the material are two key indicators. Among them, a high dielectric constant is conducive to the miniaturization of the device, while a low loss tangent is a prerequisite for low-loss communication transmission. However, in the application scenario of the terahertz frequency band, the signal is strongly absorbed by polar molecules. In conventional polymer matrices, it is difficult to have both a high dielectric constant and a low dielectric loss, which restricts the development of terahertz communication materials and devices. In addition, the regulation of dielectric properties of existing polymer composites is mainly concentrated in the low-frequency microwave band, while the technical research in related fields in the terahertz frequency band is still not in-depth and the theory is not clear.
[0003] Specifically, in the prior art, the main focus is on improving the dielectric constant to meet the use requirements of the terahertz frequency band. In the prior art, in order to improve the dielectric constant, inorganic fillers are usually doped into polymers, such as the dielectric constant adjustable composite material and flexible transmission line dielectric material disclosed in Chinese patent CN118027601A. The dielectric constant and dielectric loss of the composite material are adjusted by adding porous ceramic particles to the high molecular polymer and utilizing the pores in the porous ceramic particles, so that the dielectric constant of the composite material can be reduced or increased, thereby achieving adjustable dielectric constant of the composite material while maintaining low dielectric loss.
[0004] Another example is the thermoplastic vulcanizate-based composite material with high dielectric constant and low dielectric loss disclosed in Chinese patent CN111057311A, which increases its dielectric constant while keeping the dielectric loss at a low level by regulating the content of conductive fillers, namely carbon black, carbon nanotubes, graphite or graphite microplatelets.
[0005] However, in the prior art, when inorganic fillers are used, serious interface electric field coupling will occur between the inorganic fillers, resulting in a loss tangent that is still higher than industry expectations, making it difficult to meet the industry's application needs for miniaturized and low-loss high-frequency communication devices; in addition, when inorganic fillers are doped into polymers, local agglomeration is prone to occur, resulting in uneven quality of the final prepared composite material.
[0006] Therefore, based on the above description, there is an urgent need for a high-dielectric, low-loss composite material in the terahertz frequency band and a preparation method thereof. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, a first object of the present invention is to provide a high dielectric and low loss composite material in the terahertz frequency band.
[0008] The present invention is achieved through the following technical solutions:
[0009] A terahertz frequency band high dielectric and low loss composite material, comprising a first composite masterbatch material; the raw materials of the first composite masterbatch material are composed of a modified first high dielectric constant filler, a modified first insulating material and a non-polar polymer;
[0010] A second composite masterbatch material; the raw materials of the second composite masterbatch material are composed of a modified second high dielectric constant filler, a modified second insulating material and a non-polar polymer; and a non-polar polymer matrix;
[0011] Among them, the particle size of the first high dielectric constant filler is larger than that of the second high dielectric constant filler; the particle size of the second high dielectric constant filler is larger than that of the first insulating material and the second insulating material; the surface of the modified second high dielectric constant filler is grafted with epoxy functional groups; the surface of the modified first insulating material is grafted with siloxy groups; the surface of the modified second insulating material is grafted with epoxy functional groups and amino groups.
[0012] The mechanism of the present invention and its beneficial effects are:
[0013] By using high dielectric materials of different particle sizes and matching them with smaller insulating materials, high dielectric material particles of various sizes are arranged at intervals to block the electric field coupling between large particle materials. In addition, the introduction of high dielectric fillers of various sizes reversely helps the dispersion of insulating phase materials, further avoiding agglomeration, improving the dielectric constant while maintaining an extremely low loss tangent.
[0014] In the prior art, the pores in the porous inorganic filler are usually used to adjust the dielectric constant and dielectric loss of the composite material. However, due to the presence of the porous inorganic filler in the pore structure, the air component will inevitably be introduced in the process of incorporating it into the high molecular polymer. Since the dielectric constant of air is much lower than that of the polymer matrix and the inorganic filler, the dielectric constant of the porous inorganic filler is not increased to a large extent. Compared with the prior art, the present invention uses a "solid" filler, which can greatly increase the dielectric constant. Specifically, multi-size and multi-component high dielectric constant inorganic fillers are used to fully increase the dielectric constant, wherein smaller-sized insulating materials are used to separate high dielectric material particles, thereby blocking the electric Field coupling is achieved, thereby solving the electric field coupling problem caused by the use of multi-component inorganic fillers in the prior art; further, by separately modifying the high dielectric constant inorganic fillers and insulating materials of various sizes, the modified high dielectric constant inorganic fillers repel each other to achieve a dispersion effect, thereby improving the effect of blocking the electric field coupling. At the same time, the modified high dielectric constant inorganic fillers are spaced closer together through the modified insulating materials, thereby, compared with the prior art, not only can the use amount of high dielectric constant inorganic fillers be increased to achieve a higher dielectric constant effect, but also agglomeration can be avoided and an extremely low loss tangent can be maintained, thereby meeting the application needs of this field for miniaturized and low-loss high-frequency communication devices.
[0015] Among them, the high dielectric constant filler includes a first high dielectric constant filler and a second high dielectric constant filler, the particle size of the first high dielectric constant filler is larger than the particle size of the second high dielectric constant filler, the insulating phase material includes a first insulating material and a second insulating material, and relative to the first two high dielectric constant fillers, the insulating phases are insulating materials with smaller particle sizes, wherein fillers of various sizes are modified fillers with functional groups, and through the interaction between the functional groups, the large-sized first high dielectric constant filler and the medium-sized second high dielectric constant filler in the same system are further kept away from each other to avoid agglomeration; at the same time, between the large-sized first high dielectric constant filler and the medium-sized second high dielectric constant filler, the small-sized modified first insulating material and the modified first insulating material are used as insulating phases to fill between the large-sized first high dielectric constant filler and the medium-sized second high dielectric constant filler, and are respectively arranged around the first high dielectric constant filler and the second high dielectric constant filler, thereby improving the dispersion and uniformity of each particle size component, and ensuring that after the high dielectric constant filler is added, low loss performance can also be guaranteed.
[0016] Specifically, by using a modified first high dielectric constant filler with a surface grafted polystyrene monomer, the compatibility between the polystyrene monomer and the siloxy groups on the surface of the first insulating material is utilized, so that the first insulating material is surrounded by the first high dielectric constant filler as an insulating phase; and the second high dielectric constant filler is attracted to the epoxy groups obtained by modifying the second insulating material through the epoxy functional groups, so that the second insulating material is surrounded by the second high dielectric constant filler as an insulating phase; in addition, the large and medium-sized high dielectric constant materials (i.e., the first high dielectric constant filler and the second high dielectric constant filler) repel each other due to the polystyrene monomers and epoxy groups they possess after modification, thereby promoting the dispersion of the first high dielectric constant filler and the second high dielectric constant filler of different sizes, and further avoiding the easy agglomeration caused by the introduction of high dielectric materials of different sizes.
[0017] Furthermore, in order to improve the uniformity of the system after the first composite masterbatch material and the second composite masterbatch material are composited, the mutual attraction between the active amino groups obtained by modifying the first insulating material and the active amino groups obtained by modifying the second insulating material is achieved, so that the modified first high dielectric constant filler in the first composite masterbatch material and the modified second high dielectric constant filler in the second composite masterbatch material will not be excessively repelled; at the same time, after the first composite masterbatch material and the second composite masterbatch material are composited, the large-sized first high dielectric constant filler and the medium-sized second high dielectric constant filler in the composite system are uniformly dispersed, and there is a uniform network-like insulating phase between the two, which not only fully ensures that after using a higher content of high dielectric constant filler, the composite material will not agglomerate and cause the composite material to be uneven, but also can ensure the stability of the uniform state of the composite material during the composite processing, ultimately reducing the difficulty of the preparation process, and the prepared composite material has the excellent properties of high dielectric and low loss in the terahertz frequency band.
[0018] Furthermore, the volume ratio of the first composite masterbatch material, the second composite masterbatch material and the non-polar polymer matrix is 5:(1-4):(0.3-1.5).
[0019] Furthermore, in the first composite masterbatch material, the volume ratio of the modified first high dielectric constant filler, the modified first insulating material and the non-polar polymer is (0.20~0.60):(0.05~0.15):1.
[0020] Furthermore, in the second composite masterbatch material, the volume ratio of the modified second high dielectric constant filler, the modified second insulating material and the non-polar polymer is (0.20-0.60):(0.05-0.15):1.
[0021] Further, the particle size of the first high dielectric constant filler is 15 μm to 20 μm; and / or,
[0022] The particle size of the second high dielectric constant filler is 1 μm to 5 μm; and / or,
[0023] The particle size of the first insulating material is 100 nm to 500 nm; and / or,
[0024] The particle size of the second insulating material is 100 nm to 500 nm.
[0025] Furthermore, the first high dielectric constant filler includes: at least one of titanium dioxide, strontium titanate, barium titanate and magnesium titanate; and / or,
[0026] The second high dielectric constant filler comprises: at least one of aluminum oxide, magnesium titanate and titanium dioxide; and / or,
[0027] The first insulating material comprises: hollow silicon dioxide microspheres; and / or,
[0028] The second insulating material comprises: hollow silicon dioxide microspheres; and / or,
[0029] The non-polar polymer includes at least one of polypropylene and polyethylene.
[0030] In the present invention, by selecting the above high dielectric constant filler components and further optimizing the particle size range, the filler dispersion morphology can be optimized and the electric field coupling blocking effect between fillers can be maximized, thereby achieving the expected effects of high dielectric constant and low loss tangent at the same time, and being able to meet the requirements of high dielectric and low loss in the terahertz frequency band.
[0031] Compared with the prior art using porous fillers to control the dielectric constant, the dielectric constant of the present invention is improved to a greater extent; compared with the prior art using conductive fillers to control the dielectric constant, the present invention can block electric field coupling, thereby solving the defect of using conductive fillers to generate strong electric field coupling.
[0032] The second object of the present invention is to provide a method for preparing the above-mentioned terahertz frequency band high dielectric and low loss composite material, comprising the following steps:
[0033] S1, melt-blending the modified first high dielectric constant filler, the modified first insulating material and the non-polar polymer to obtain a first composite masterbatch material;
[0034] S2, melt-blending the modified second high dielectric constant filler, the modified second insulating material and the non-polar polymer to obtain a second composite masterbatch material;
[0035] S3, subjecting the first composite masterbatch material, the second composite masterbatch material and the non-polar polymer matrix to multiple melt blending and thermoforming treatments to obtain a composite material.
[0036] Furthermore, the preparation method of the modified first high dielectric constant filler comprises:
[0037] S11, mixing a first high dielectric constant filler, a first silane coupling agent and a solvent to obtain a functionalized filler; the first silane coupling agent is at least one of octadecyltrichlorosilane, octadecyldimethylchlorosilane and octadecyltrimethoxysilane;
[0038] S12, mixing the functionalized filler, styrene monomer and initiator to graft polystyrene on the surface of the functionalized filler to obtain a modified first high dielectric constant filler.
[0039] Furthermore, the preparation method of the modified second high dielectric constant filler comprises:
[0040] S21. Mix the pretreated second high dielectric constant filler, the second silane coupling agent and the solvent to modify the surface of the second high dielectric constant filler to obtain a modified second high dielectric constant filler; the second silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-epoxypropyltrimethoxysilane.
[0041] Furthermore, the preparation method of the modified first insulating material comprises:
[0042] s11, mixing the pretreated first insulating material, a third silane coupling agent and a solvent to perform a first surface modification to obtain a functionalized insulating material; the third silane coupling agent is at least one of octadecyltrichlorosilane, octadecyldimethylchlorosilane and octadecyltrimethoxysilane;
[0043] s12. Mix the functionalized insulating material, a fourth silane coupling agent and a solvent to perform a second surface modification to obtain a modified first insulating material; the fourth silane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-aminopropyldimethoxyvinylsilane.
[0044] Furthermore, the preparation method of the modified second insulating material comprises:
[0045] s21, mixing the pretreated second insulating material, the fifth silane coupling agent and the solvent to perform a first surface modification to obtain a functionalized insulating material; the fifth silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-epoxypropyltrimethoxysilane;
[0046] s22. Mix the functionalized insulating material, the sixth silane coupling agent and the solvent to perform a second surface modification to obtain a modified second insulating material; the sixth silane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-aminopropyldimethoxyvinylsilane. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0048] Figure 1 This is a SEM image of the terahertz frequency band high dielectric and low loss composite material provided in Example 1 of the present invention at 10,000 times magnification;
[0049] Figure 2 This is a SEM image of the terahertz frequency band high dielectric and low loss composite material provided in Example 1 of the present invention at 20,000 times magnification. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0051] Example 1
[0052] This embodiment provides a method for preparing a high-dielectric, low-loss composite material in the terahertz frequency band, comprising the following steps:
[0053] (1) The titanium dioxide powder and hollow silica microspheres are subjected to surface functionalization treatment to complete chemical modification of the polystyrene system, and the filler and the polypropylene matrix are melt-blended using a twin-screw device to obtain a first composite masterbatch material. The specific implementation steps are as follows:
[0054] Filler particle size selection:
[0055] The first high dielectric constant filler is titanium dioxide powder with a particle size of 18 μm, and the first insulating material is hollow silicon dioxide microspheres with a particle size of 300 nm.
[0056] Chemical modification of the surface of titanium dioxide filler: octadecyltrichlorosilane was dissolved in toluene solvent to form a 5 vol% solution; titanium dioxide powder was added to the solution and stirred at room temperature for 4 hours to functionalize its surface; the functionalized titanium dioxide powder was dried in a vacuum oven at 100°C for 6 hours.
[0057] A polystyrene coating layer is grafted onto the surface of titanium dioxide powder: functionalized titanium dioxide powder is mixed with polystyrene monomer (styrene) and initiator azobisisobutyronitrile (AIBN) in a weight ratio of 1:10, and toluene solvent is added to the mixture; the mixture is deoxygenated by purging with nitrogen for 30 minutes, the mixture is heated to 70°C, and the temperature is maintained for 6 hours while stirring; the precipitate is collected by filtration or centrifugation, the grafted titanium dioxide powder is washed with ethanol, and dried in a vacuum oven at 100°C for 6 hours to complete the surface polystyrene grafting and obtain a modified first high dielectric constant filler.
[0058] Surface chemical modification of hollow silica microsphere filler: The surface modification treatment is divided into two wet processes, including:
[0059] First surface modification: dry hollow silica microspheres were added to a 5 vol% octadecyltrichlorosilane solution (toluene solvent), and the mixture was stirred at room temperature for 24 hours; after the reaction, the product was filtered and washed with toluene solvent to remove unreacted silane; the modified inorganic powder was dried in a vacuum oven at 100°C for 6 hours to complete the first surface modification;
[0060] Second surface modification: add the dried modified hollow silica microspheres to a 5 vol% 3-aminopropyltriethoxysilane solution (toluene solvent), and stir the mixture at room temperature for 24 hours; after the reaction, filter and wash the inorganic powder with toluene solvent to remove unreacted silane; dry the modified inorganic powder in a vacuum oven at 100°C for 6 hours to complete the second surface modification and obtain a modified first insulating material.
[0061] The modified first high dielectric constant filler, the modified first insulating material and the polypropylene matrix are melt-blended: 500g of polypropylene masterbatch is weighed, and the volume ratio of the modified first high dielectric constant filler, the modified first insulating material and the polypropylene is 0.40:0.05:1; the components are mechanically blended at a speed of 300 rpm, 5 min each time, and divided into 3 times; the mixed raw materials are added into a twin-screw equipment, the twin-screw processing temperature is 220°C, and the screw speed is 300 rpm; the mixed composite material melt is extruded-water-cooled and pelletized, and the granulated composite material masterbatch is dried in a vacuum drying oven for 6 hours at a drying temperature of 80°C to obtain the first composite masterbatch material.
[0062] (2) The magnesium titanate powder and the hollow silica microspheres are subjected to surface functionalization treatment respectively to complete the chemical modification of the epoxy system, and the filler and the polypropylene matrix are melt-blended by a twin-screw device to obtain a second composite masterbatch material. The specific implementation steps are as follows:
[0063] Selection of filler particle size: The second highest dielectric constant filler is magnesium titanate powder with a particle size of 3 μm, and the second insulating material is hollow silica microspheres with a particle size of 300 nm.
[0064] Chemical modification of the surface of magnesium titanate filler: Add the dried magnesium titanate powder to a 5 vol% 3-glycidyloxypropyltrimethoxysilane solution, and stir the mixture at room temperature for 24 hours. After the reaction is completed, filter and wash the inorganic powder with toluene solvent to remove unreacted silane; dry the modified inorganic powder in a vacuum oven at 100°C for 6 hours to complete the surface modification of the magnesium titanate filler.
[0065] Surface chemical modification of hollow silica microsphere filler: The surface modification treatment is divided into two wet processes, including:
[0066] First surface modification: dry hollow silica microspheres were added to a 5 vol% 3-glycidyloxypropyltrimethoxysilane solution (toluene solvent), and the mixture was stirred at room temperature for 24 hours; after the reaction, the inorganic powder was filtered and washed with toluene solvent to remove unreacted silane; the modified inorganic powder was dried in a vacuum oven at 100°C for 6 hours to complete the first surface modification.
[0067] Second surface modification: Add the dried modified hollow silica microspheres to a 5 vol% 3-aminopropyltriethoxysilane solution (toluene solvent), and stir the mixture at room temperature for 24 hours. After the reaction is completed, filter and wash the inorganic powder with toluene solvent to remove unreacted silane; dry the modified inorganic powder in a vacuum oven at 100°C for 6 hours to complete the second surface modification.
[0068] Melt blending of modified second high dielectric constant filler, modified second insulating material and polypropylene matrix: weigh 500 g of polypropylene masterbatch, and the volume ratio of the modified second high dielectric constant filler, modified second insulating material and polypropylene used is 0.40:0.05:1; mechanically blend the components at a speed of 300 rpm, 5 min each time, and divided into 3 times; add the mixed raw materials into a twin-screw equipment, the twin-screw processing temperature is 220°C, and the screw speed is 300 rpm; the mixed composite material melt is extruded and water-cooled and pelletized, and the granulated composite material masterbatch is dried in a vacuum drying oven for 6 hours at a drying temperature of 80°C to obtain the first composite masterbatch material.
[0069] (3) The dried first composite masterbatch material, the second composite masterbatch material and the polypropylene material are cyclically blended to prepare a composite sample. The specific implementation steps are as follows:
[0070] Twin-screw cyclic blending: The volume ratio of the weighed first composite masterbatch material, the second composite masterbatch material and the polypropylene matrix is 5:2:0.3; the components are mechanically blended at a speed of 300 rpm for 5 min each time, divided into 3 times. The mixed raw materials are added to the twin-screw equipment, the twin-screw processing temperature is 220°C, and the screw speed is 300 rpm. The obtained composite particles are added back to the twin-screw and cyclically blended twice.
[0071] Hot pressing molding of composite sample sheets: Place the composite material masterbatch obtained in step 3 in a hot pressing molding mold, with a plasticizing temperature of 220°C, a plasticizing time of 15 min, a hot pressing temperature of 220°C, a holding pressure of 200 Mpa, a holding time of 5 min, and a cooling time of 5 min to prepare a composite sample sheet.
[0072] Example 2
[0073] The difference between this embodiment and embodiment 1 is that the volume ratio of modified titanium dioxide filler, modified hollow silica microspheres and polypropylene used in the first composite masterbatch material is 0.60:0.05:1; the volume ratio of modified magnesium titanate filler, modified hollow silica microspheres and polypropylene used in the second composite masterbatch material is 0.60:0.05:1.
[0074] Example 3
[0075] The difference between this embodiment and embodiment 1 is that the volume ratio of modified titanium dioxide filler, modified hollow silica microspheres and polypropylene used in the first composite masterbatch material is 0.20:0.05:1; the volume ratio of modified magnesium titanate filler, modified hollow silica microspheres and polypropylene used in the second composite masterbatch material is 0.20:0.05:1.
[0076] Example 4
[0077] The difference between this embodiment and embodiment 1 is that in this embodiment, the first high dielectric constant filler is selected from titanium dioxide powder with a particle size of 15 μm, and the first insulating material is selected from hollow silica microspheres with a particle size of 100 nm; the second high dielectric constant filler is selected from magnesium titanate powder with a particle size of 1 μm, and the second insulating material is selected from hollow silica microspheres with a particle size of 100 nm.
[0078] Example 5
[0079] The difference between this embodiment and embodiment 1 is that in this embodiment, the first high dielectric constant filler is selected from titanium dioxide powder with a particle size of 20 μm, and the first insulating material is selected from hollow silica microspheres with a particle size of 500 nm; the second high dielectric constant filler is selected from magnesium titanate powder with a particle size of 5 μm, and the second insulating material is selected from hollow silica microspheres with a particle size of 500 nm.
[0080] Example 6
[0081] The difference between this embodiment and embodiment 1 is that, in this embodiment, chemical modification of the polystyrene system is completed by surface functionalization treatment of strontium titanate powder and hollow silica microspheres, and the filler and the polypropylene matrix are melt-blended using a twin-screw device to obtain a first composite masterbatch material; chemical modification is completed by surface functionalization treatment of alumina powder and hollow silica microspheres, and the filler and the polypropylene matrix are melt-blended using a twin-screw device to obtain a second composite masterbatch material.
[0082] Example 7
[0083] The difference between this embodiment and embodiment 1 is that, in this embodiment, chemical modification of the polystyrene system is completed by surface functionalization treatment of barium titanate powder and hollow silica microspheres, and the filler and the polypropylene matrix are melt-blended by a twin-screw device to obtain a first composite masterbatch material; chemical modification is completed by surface functionalization treatment of titanium dioxide powder and hollow silica microspheres, and the filler and the polypropylene matrix are melt-blended by a twin-screw device to obtain a second composite masterbatch material.
[0084] Example 8
[0085] The difference between this embodiment and embodiment 1 is that, in the surface chemical modification of titanium dioxide filler, octadecyldimethylchlorosilane is used to replace octadecyltrichlorosilane; in the surface chemical modification of magnesium titanate filler, γ-methacryloxypropyltrimethoxysilane is used to replace 3-glycidyloxypropyltrimethoxysilane; in the surface chemical modification of the first insulating material, i.e., hollow silica microsphere filler, octadecyltrichlorosilane in the first surface modification is replaced by octadecyldimethylchlorosilane; 3-aminopropyltrimethoxysilane is used to replace 3-aminopropyltriethoxysilane in the second modification; in the surface chemical modification of the second insulating material, i.e., hollow silica microsphere filler, γ-methacryloxypropyltrimethoxysilane is used to replace 3-glycidyloxypropyltrimethoxysilane in the first surface modification; 3-aminopropyltrimethoxysilane is used to replace 3-aminopropyltriethoxysilane in the second modification.
[0086] Example 9
[0087] The difference between this embodiment and embodiment 1 is that, in the surface chemical modification of titanium dioxide filler, octadecyltrimethoxysilane is used to replace octadecyltrichlorosilane; in the surface chemical modification of magnesium titanate filler, 3-epoxypropyltrimethoxysilane is used to replace 3-glycidyloxypropyltrimethoxysilane; in the surface chemical modification of the first insulating material, i.e., hollow silica microsphere filler, octadecyltrimethoxysilane is used to replace octadecyltrichlorosilane in the first surface modification; 3-aminopropyldimethoxyvinylsilane is used to replace 3-aminopropyltriethoxysilane in the second modification; in the surface chemical modification of the second insulating material, i.e., hollow silica microsphere filler, 3-epoxypropyltrimethoxysilane is used to replace 3-glycidyloxypropyltrimethoxysilane in the first surface modification; 3-aminopropyldimethoxyvinylsilane is used to replace 3-aminopropyltriethoxysilane in the second modification.
[0088] Comparative Example 1
[0089] In this comparative example, the first high dielectric constant filler is still titanium dioxide powder, the second high dielectric constant filler is still magnesium titanate powder, and the small-size insulating phase material is still silica microspheres; the filler particle size and content are the same as those in Example 1, but no chemical modification of the filler surface is performed; the blending processing steps and dielectric testing process are the same as those in Example 1.
[0090] Comparative Example 2
[0091] In this comparative example, the first high dielectric constant filler is still selected from titanium dioxide powder, the first insulating material is still selected from silica microspheres, and the second high dielectric constant filler component is not used; the filler particle size is the same as that in Example 1, and only the first high dielectric constant filler and small-sized hollow silica microspheres are chemically modified by the polystyrene system; the filler and the polymer masterbatch are directly blended to prepare a composite sample, and the volume ratio of the modified first high dielectric constant filler, the modified first insulating material and the polypropylene used is 0.20:0.05:1; the modification, blending and thermoforming processing steps and the dielectric testing process are the same as those in Example 1.
[0092] Comparative Example 3
[0093] In this comparative example, the second high dielectric constant filler is still selected from magnesium titanate powder, the second insulating material is still selected from silica microspheres, and the first high dielectric constant filler component is not used; the filler particle size is the same as that in Example 1, and only the second high dielectric constant filler and small-sized hollow silica microspheres are chemically modified by the epoxy system; the filler and the polymer masterbatch are directly blended to prepare a composite sample, and the volume ratio of the modified second high dielectric constant filler, the modified second insulating material and the polypropylene used is 0.20:0.05:1; the modification, blending and thermoforming processing steps and the dielectric testing process are the same as those in Example 1.
[0094] Comparative Example 4
[0095] In this comparative example, the first high dielectric constant filler is still selected from titanium dioxide powder, the second high dielectric constant filler is still selected from magnesium titanate powder, and the second insulating material is not added; the filler particle size is the same as that in Example 1, and the first high dielectric constant filler and the second high dielectric constant filler are not chemically modified; the volume ratio of the first high dielectric constant filler to the polypropylene material in the first composite masterbatch material is 0.2:1, and the volume ratio of the second high dielectric constant filler to the polypropylene material in the second composite masterbatch material blend is 0.2:1; the volume ratio of the weighed first composite masterbatch material, the second composite masterbatch material and the polypropylene matrix is the same as that in Example 1 (5:2:0.3).
[0096] Comparative Example 5
[0097] In this comparative example, titanium dioxide powder and magnesium titanate powder are still selected as high dielectric constant fillers, and silicon dioxide microspheres are still selected as insulating phase fillers; the filler particle size is set to 18 μm, and no gradient particle size control is performed. The content of each component filler is the same as in Example 1, and the high dielectric constant filler and small-sized hollow silicon dioxide microspheres are chemically modified, and the chemical modification process is the same as in Example 1; the blending processing steps and dielectric test process are the same as in Example 1.
[0098] Comparative Example 6
[0099] In this comparative example, only barium titanate powder is selected as a high dielectric constant filler, and no multi-component filler is used for blending; the filler particle size is 18 μm, and the volume ratio to the polypropylene matrix material is 0.10:1; the filler is not chemically modified; the blending processing steps and dielectric testing process are the same as those in Example 1.
[0100] Test example
[0101] The polymer composite sample sheets prepared in Examples 1-9 and Comparative Examples 1-6 were polished, and their dielectric properties at 100 GHz, 200 GHz, 300 GHz, and 400 GHz were tested using terahertz time-domain spectroscopy to detect their dielectric constants (Dk) and dielectric loss factors (Df). The test results are shown in Table 1 below:
[0102] Table 1
[0103]
[0104] As shown in the attached figure of the specification Figure 1 and Figure 2 As shown, taking the composite sample prepared in Example 1 as an example, observing its SEM images at 10,000 times and 20,000 times magnification, it can be seen from the figure that in the prepared composite sample, the gradient particle size modified filler is arranged in a preset form, and the insulating phase filler after surface functionalization modification is uniformly surrounded by the modified first high dielectric constant filler and the modified second high dielectric constant filler, playing the expected effect of blocking electric field coupling and optimizing the distribution morphology of high dielectric fillers. Further, according to Table 1 above, it can be seen from Example 1, Examples 4-5 and Comparative Example 1 that compared with the existing composite process of doping multi-component high dielectric constant fillers, the present invention can reduce the loss by more than 85% on the basis of adjusting the composite material to a higher dielectric constant by realizing surface multifunctional modification between multi-component fillers, and has obvious advantages of high dielectric constant and low loss tangent performance in the terahertz frequency band.
[0105] It can be seen from Examples 1-3, Examples 6-9 and Comparative Example 2 that, compared with the existing composite process of co-doping a single high dielectric constant filler with hollow silica microspheres, the present invention, by adopting modified high dielectric constant fillers of multiple particle sizes and combining them with modified insulating fillers, can reduce the loss by more than 68% while increasing the dielectric constant of the composite material by 43%, and has obvious advantages in high dielectric constant and low loss tangent performance in the terahertz frequency band.
[0106] It can be seen from Examples 1-3, Examples 6-9 and Comparative Example 3 that, compared with the existing composite process of co-doping a single high dielectric constant filler with hollow silica microspheres, the present invention, by adopting modified high dielectric constant fillers of multiple particle sizes and combining them with modified insulating fillers, can reduce the loss by more than 55% while increasing the dielectric constant of the composite material by 55%, and has obvious advantages in high dielectric constant and low loss tangent performance in the terahertz frequency band.
[0107] It can be seen from Examples 1-7 and Comparative Example 4 that, compared with the existing composite process of co-doping multiple high dielectric constant fillers, the present invention, by adopting modified high dielectric constant fillers of multiple particle sizes and combining them with modified insulating fillers, can reduce the loss by more than 75% while increasing the dielectric constant of the composite material by 53%, and has obvious advantages in high dielectric constant and low loss tangent performance in the terahertz frequency band.
[0108] It can be seen from Example 1, Examples 4-5 and Comparative Example 5 that, compared with composite materials doped with multiple fillers without achieving particle size matching, the present invention, by adopting modified high dielectric constant fillers with multiple particle sizes and combining modified insulating fillers, can reduce the loss tangent by more than 73% on the basis of adjusting the dielectric constant of the composite material to a higher level, and has obvious advantages of high dielectric constant and low loss tangent performance in the terahertz frequency band.
[0109] It can be seen from Example 7 and Comparative Example 6 that, compared with the existing composite materials doped with a single high dielectric constant filler, the present invention, by adopting modified high dielectric constant fillers with multiple particle sizes and combining them with modified insulating fillers, can reduce the loss by more than 88% while increasing the dielectric constant of the composite material by 57%, and has obvious advantages in high dielectric constant and low loss tangent performance in the terahertz frequency band.
[0110] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high dielectric and low loss composite material in the terahertz frequency band, characterized in that: include: A first composite masterbatch material; the raw materials of the first composite masterbatch material are composed of a modified first high dielectric constant filler, a modified first insulating material and a non-polar polymer; A second composite masterbatch material; the raw materials of the second composite masterbatch material are composed of a modified second high dielectric constant filler, a modified second insulating material and a non-polar polymer; and a non-polar polymer matrix; Wherein, the particle size of the first high dielectric constant filler is larger than that of the second high dielectric constant filler; the particle size of the second high dielectric constant filler is larger than that of the first insulating material and the second insulating material; The particle size of the first high dielectric constant filler is 15 μm to 20 μm; The particle size of the second high dielectric constant filler is 1 μm to 5 μm; The particle size of the first insulating material is 100 nm to 500 nm; The particle size of the second insulating material is 100 nm to 500 nm; The preparation method of the modified first high dielectric constant filler comprises: A first high dielectric constant filler, a first silane coupling agent and a solvent are mixed to obtain a functionalized filler; the first silane coupling agent is at least one of octadecyltrichlorosilane, octadecyldimethylchlorosilane and octadecyltrimethoxysilane; The functionalized filler, styrene monomer and initiator are mixed to graft polystyrene on the surface of the functionalized filler to obtain a modified first high dielectric constant filler; The surface of the modified second high dielectric constant filler is grafted with epoxy functional groups; the surface of the modified first insulating material is grafted with siloxy groups and amino groups; the surface of the modified second insulating material is grafted with epoxy functional groups and amino groups.
2. The terahertz frequency band high dielectric and low loss composite material according to claim 1, characterized in that: The volume ratio of the first composite masterbatch material, the second composite masterbatch material and the non-polar polymer matrix is 5:(1-4):(0.3-1.5).
3. The terahertz frequency band high dielectric and low loss composite material according to claim 1, characterized in that: In the first composite masterbatch material, the volume ratio of the modified first high dielectric constant filler, the modified first insulating material and the non-polar polymer is (0.20~0.60):(0.05~0.15):1; in the second composite masterbatch material, the volume ratio of the modified second high dielectric constant filler, the modified second insulating material and the non-polar polymer is (0.20~0.60):(0.05~0.15):
1.
4. The terahertz frequency band high dielectric and low loss composite material according to claim 1, characterized in that: The first high dielectric constant filler comprises: at least one of titanium dioxide, strontium titanate, barium titanate and magnesium titanate; and / or, The second high dielectric constant filler comprises: at least one of aluminum oxide, magnesium titanate and titanium dioxide; and / or, The first insulating material comprises: hollow silicon dioxide microspheres; and / or, The second insulating material comprises: hollow silicon dioxide microspheres; and / or, The non-polar polymer includes at least one of polypropylene and polyethylene.
5. A method for preparing a terahertz frequency band high dielectric and low loss composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, melt-blending the modified first high dielectric constant filler, the modified first insulating material and the non-polar polymer to obtain a first composite masterbatch material; S2, melt-blending the modified second high dielectric constant filler, the modified second insulating material and the non-polar polymer to obtain a second composite masterbatch material; S3, subjecting the first composite masterbatch material, the second composite masterbatch material and the non-polar polymer matrix to multiple melt blending and thermoforming treatments to obtain a composite material.
6. The method for preparing a terahertz frequency band high dielectric and low loss composite material according to claim 5, characterized in that: The preparation method of the modified second high dielectric constant filler comprises: S21. Mix the pretreated second high dielectric constant filler, the second silane coupling agent and the solvent to modify the surface of the second high dielectric constant filler to obtain a modified second high dielectric constant filler; the second silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-epoxypropyltrimethoxysilane.
7. The method for preparing a terahertz frequency band high dielectric and low loss composite material according to claim 5, characterized in that: The preparation method of the modified first insulating material comprises: s11, mixing the pretreated first insulating material, a third silane coupling agent and a solvent to perform a first surface modification to obtain a functionalized insulating material; the third silane coupling agent is at least one of octadecyltrichlorosilane, octadecyldimethylchlorosilane and octadecyltrimethoxysilane; s12. Mix the functionalized insulating material, a fourth silane coupling agent and a solvent to perform a second surface modification to obtain a modified first insulating material; the fourth silane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-aminopropyldimethoxyvinylsilane.
8. The method for preparing a terahertz frequency band high dielectric and low loss composite material according to claim 5, characterized in that: The preparation method of the modified second insulating material comprises: s21, mixing the pretreated second insulating material, the fifth silane coupling agent and the solvent to perform a first surface modification to obtain a functionalized insulating material; the fifth silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-epoxypropyltrimethoxysilane; s22. Mix the functionalized insulating material, the sixth silane coupling agent and the solvent to perform a second surface modification to obtain a modified second insulating material; the sixth silane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-aminopropyldimethoxyvinylsilane.
Citation Information
Patent Citations
Thermoplastic vulcanized rubber-based composite material with high dielectric constant and low dielectric loss, and preparation method thereof
CN111057311A
Composite material with adjustable dielectric constant, flexible transmission line dielectric material and electronic equipment
CN118027601A
Dielectric and method of manufacturing same
WO2024075791A1